О медленном росте трещины с контактирующими берегами в вязкоупругом теле - Селиванов, М.Ф. (Прикладная механика, 2017)
Объектом исследования данной работы является кинетика роста сквозной трещины нормального отрыва в бесконечной пластине, материал которой обладает наследственными свойствами. Исследуем квазистатический устойчивый рост имеющейся к моменту приложения нагрузки трещины. Распространение трещины происходит в изотермических условиях при постоянном докритическом уровне внешней нагрузки вследствие вязкоупругих свойств материала пластины. Запропоновано алгоритм розв’язання задачі про повільне поширення тріщини нормального відриву з частковою зоною контакту берегів. В основу алгоритму покладено модель тріщини з зоною зчеплення, ітеративний метод побудови розв’язку для пружного розкриття і принцип пружно-в’язкопружної аналогії, який дозволяє записати залежне від часу розкриття в формі Больцмана  Вольтерра. Як критерій поширення тріщини, використано деформаційний критерій зі сталою величиною критичного розкриття і міцності зчеплення протягом квазістатичного росту тріщини. Алгоритм проілюстровано числовим прикладом із розтягуючим на нескінченності зусиллям і симетричною відносно лінії тріщини системою двох зосереджених сил, що викликають контакт берегів. При поширенні тріщини зона контакту берегів зникає, що супроводжується швидким переходом до динамічного етапу поширення. An algorithm of solving the problem on slow growth of mode I crack propagation with a partial zone of the crack faces contact is proposed. This algorithm is based on the cohesive crack model, the iterative method of constructing the solution elastic for elastic opening displacement, and the correspondence principle that allows to write the depending on time opening displacement in the Boltzmann-Volterra form. As a fracture criterion, the deformation criterion with constant values of critical opening displacement and the cohesive strength during the quasi-static crack growth is used. This algorithm is illustrated by a numerical example for the problem with tensile loading at infinity and the pair of symmetrically applied point forces that cause the crack faces contact. When the crack being propagated, then the zone of crack faces contact is vanished what is accompanied by the fast transition to the dynamic fracture.